2022
DOI: 10.1002/adfm.202201394
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Ions Direct the Solid‐State Transformation of Amorphous Calcium Carbonate Thin Films to Aragonite, Magnesium‐Calcite, or Dolomite

Abstract: Amorphous calcium carbonate (ACC) is a common precursor to crystalline calcium carbonate, and is of particular importance in biomineralization, where its crystallization in privileged environments ensures a pseudomorphic transformation. While organisms regulate this process using organic molecules and magnesium ions to selectively form calcite or aragonite, it has proven highly challenging to replicate this polymorph selectivity synthetically. Here, it is demonstrated that remarkable control can be achieved ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…Traditional XRD con rms these results from molded samples as seen in Figure S12. This result is consistent with results obtained by forming these minerals in bulk 49,50 , suggesting that knowhow on polymorphic control of CaCO 3 formation in bulk aqueous solutions can be transferred to our process.…”
Section: Resultssupporting
confidence: 92%
“…Traditional XRD con rms these results from molded samples as seen in Figure S12. This result is consistent with results obtained by forming these minerals in bulk 49,50 , suggesting that knowhow on polymorphic control of CaCO 3 formation in bulk aqueous solutions can be transferred to our process.…”
Section: Resultssupporting
confidence: 92%
“…388 Such an effect of Mg 2+ can be attributed to strong and well-hydrated Mg 2+ cations that can delay the nucleation and growth of calcite and can either be incorporated within the calcite lattice to create a barrier to prevent the further growth of calcite nuclei. 389,390 cystoliths. 391 In these cystoliths, a high SiO 4 4À content in the ACC correlated with high thermal stability.…”
Section: Preparation and Stabilization Of Accmentioning
confidence: 99%
“…388 Such an effect of Mg 2+ can be attributed to strong and well-hydrated Mg 2+ cations that can delay the nucleation and growth of calcite and can either be incorporated within the calcite lattice to create a barrier to prevent the further growth of calcite nuclei. 389,390 Anions such as SiO 4 4− , PO 4 3− , and OH − also influence the stability of ACC. The role of SiO 4 4− in stabilizing ACC has been evidenced by the presence of SiO 4 4− in cystoliths.…”
Section: Amorphous Calcium Carbonatementioning
confidence: 99%
“…On the other hand, ACC easily crystallizes into calcite by heating in air . This crystallization process is considered to proceed by solid-state transformation. ,, The crystallization by solid-state transformation has a variety of applications, including the study of biominerals, , selective crystallization into desired polymorphs (calcite ,, or aragonite , ), the addition of large amounts of impurities to crystals, reference materials, and synthesis of nanoporous calcite with a high specific surface area …”
Section: Introductionmentioning
confidence: 99%
“…This thermodynamic reaction prevents the crystallization of ACMC by heating at ca. 400 °C in air, although a recent study reported the dolomite synthesis from a thin film of ACMC by heating in air . On the other hand, ACMC does not crystallize into dolomite at ambient temperature because of the kinetic barriers. , Therefore, most previous studies have conducted the dolomitization of ACMC via dissolution-reprecipitation in hydrothermal solution. , …”
Section: Introductionmentioning
confidence: 99%